What's information got to do with it? Third-party voting in plurality systems. (July 2016) - Raymond, Christopher D; Tromborg, Mathias Wessel
Although strategic voting theory predicts that the number of parties will not exceed two in single-member district plurality systems, the observed number of parties often does. Previous research suggests that the reason why people vote for third parties is that they possess inaccurate information about the parties' relative chances of winning. However, research has yet to determine whether third-party voting persists under conditions of accurate information. In this article, we examine whether possessing accurate information prevents individuals from voting for third-placed parties in the 2005 and 2010 British elections. We find that possessing accurate information does not prevent most individuals from voting for third-placed parties and that many voters possess reasonably accurate information regarding the viability of the parties in their constituencies. These findings suggest that arguments emphasizing levels of voter information as a major explanation for why multiparty systems often emerge in plurality systems are exaggerated.